PROGNOSTIC FACTORS FOR LOCOREGIONAL RECURRENCES AFTER SUPRACRICOID LARYNGECTOMY - Samac, Ksenija; Čanji, Karol; Jović, Rajko; Kljajić, Vladimir; Tovilović, Vanja; Sivčev, Ivan; Bogdanović, Mladen; Đurović, Vladimir; Zbućnović, Dušan (Acta medicae Medianae, 2026)
Supracricoid laryngectomy, also named open partial horizontal laryngectomy type II (OPH II), involves resection of the ventricular folds, vocal folds, paraglottic space, thyroid cartilage, optionally up to one arytenoid cartilage, and, depending on whether it is an OPH II A or B, of the epiglottis. Locoregional control of the disease is a complex phenomenon that includes the characteristics of the tumor, the patient and genetic factors. This study aimed to identify factors indicating an increased possibility of locoregional recurrences following supracricoid laryngectomy.Retrospective study included 104 patients who underwent supracricoid laryngectomy at the Otorhinolaryngology and Head and Neck Surgery Clinic of the University Clinical Center of Vojvodina in the period 2002–2020. Pathohistologically verified TN stage, thyroid cartilage invasion, positive margins, vascular invasion, positive Delphi lymph node and extranodal extension of metastatic disease were estimated as predictive factors for locoregional recurrences.The median time for a local recurrence was 22 months (9.5–59.5), and the median time for regional recurrence was 21 months (10–38.5). Statistical significance in local recurrences of the disease was recorded in the presence of pathohistologically confirmed positive margins (p = 0.033) and vascular invasion (p = 0.029). The statistical significance of vascular invasion was also observed in regional (p = 0.041) and locoregional recurrences (p = 0.004). Pathohistologically confirmed higher T stage showed statistical significance in the occurrence of regional metastases (p = 0.035).Pathohistologically confirmed vascular invasion stands out as an independent factor that should be paid attention to in further postoperative therapeutic care in order to achieve high-quality locoregional control of the disease, while in local control, along with vascular invasion, the importance of positive resection margins is also emphasized.
Keywords: laryngeal carcinoma, organ preservative protocol, open partial horizontal laryngectomy type II, supracricoid laryngectomy